A clearer understanding of the dynamic structuring of different natural rubber genotypes on a macroscopic and mesoscopic scale by asymmetrical-flow field-flow fractionation (A4F) analysis - Siriluck Liengprayoon; Christine Char; Laurent Vaysse; Frédéric Bonfils (Polymer Testing)
Unlike synthetic elastomers, the structure of natural rubber (NR) evolves (dynamic structuring) and so do its properties during the storage before reaching an industrial mixer. In the rubber industry this is known as storage hardening. NR samples from three genotypes (GT1, RRIM600 and PB235) were subjected to different levels of structuring by varying the structuring time (t) on phosphorus pentoxide (0 < t < 28 h). Storage hardening (ΔP) of the samples was then determined by measuring the increase in Wallace plasticity (P) (macro-scale) and by analyzing their mesostructure (meso-scale) using asymmetrical flow field flow fractionation (A4F). Monitoring ΔP as a function of structuring time revealed a diversity of behaviors specific to the genotype from which the rubber originated. For example, NR samples from genotypes GT1 and PB235 exhibited different kinetics for t < 12 h, an increase in ΔP with structuring time, but reached the same final plateau (t > 12 h). An A4F analysis of the samples was used to quantify the fraction of microaggregates smaller than 1 μm (microgel<1μ). The microgel<1μ rate decreased with structuring time to varying extents depending on the genotype. A very significant negative relationship was found between ΔP and the microgel<1μ rate, indicating that the NR samples that hardened the most contained the lowest microgel<1μ rate, but the highest macrogel rate.